The effect of CTL learning model and learning style on the historical learning outcomes - Syahra, Inda; Sarkadi, Sarkadi; Ibrahim, Nurzengky (Harmoni Sosial: Jurnal Pendidikan IPS, 2020)
This study aims to obtain the influence of learning models and learning styles on historical learning outcomes. Students are given a CTL and conventional learning model by measuring visual learning styles and auditory learning styles. This type of research is a quantitative study using an experimental method with a 2 x 2 factorial design. The population is all students of class X 2019/2020 school year. The sampling technique used is multistage random sampling. Class X-A as an experimental class and grade X-B as a control class with a total of 70 students construct validity is analyzed by the correlation between items using Product Moment Correlation, and Cronbach’s alpha formula tested reliability. The results showed that learning outcomes with the CTL learning model were higher than conventional learning models. While student learning outcomes using visual learning styles are more effective than auditory learning styles. There is a relationship between learning models with learning styles.